2020
DOI: 10.3390/ijms21072615
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Modeling of Telocytes Behavior in Signaling and Intercellular Communication Processes

Abstract: Background: Telocytes (TCs) are unique interstitial or stromal cells of mesodermal origin, defined by long cellular extensions called telopodes (Tps) which form a network, connecting them to surrounding cells. TCs were previously found around stem and progenitor cells, and were thought to be most likely involved in local tissue metabolic equilibrium and regeneration. The roles of telocytes are still under scientific scrutiny, with existing studies suggesting they possess various functions depending on their lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…The most obvious function of this network in the gut is to be a scaffold that guarantees mechanical and rheological support to the connective components during peristalsis and maintains the integrity of the ganglia ( Figure 1 ) during bowel movements aimed at digestion or absorption [ 16 , 17 , 21 ]. This function is particularly evident in the gut submucosa where the TCs form a dense network [ 15 , 16 , 17 ].…”
Section: Telocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious function of this network in the gut is to be a scaffold that guarantees mechanical and rheological support to the connective components during peristalsis and maintains the integrity of the ganglia ( Figure 1 ) during bowel movements aimed at digestion or absorption [ 16 , 17 , 21 ]. This function is particularly evident in the gut submucosa where the TCs form a dense network [ 15 , 16 , 17 ].…”
Section: Telocytesmentioning
confidence: 99%
“…For example, Vannucchi and coworkers showed the presence of three subtypes of TCs in human urinary bladder lamina propria based on either IHC or TEM observations and each subtype was supposed to play a proper role [ 10 ]. Kurahashi et al [ 21 ] reported that the cells at the bottom of crypts were more sparse and showed lower PDGFRα-positivity, while the cells near the apex of the villi were denser and showed higher PDGFRα labeling intensity. Intriguingly, Shoshkes-Carmel et al [ 55 ], Kondo and Koestner, [ 57 ], and Koestner [ 58 ], using genetic methodologies, distinguished between the TCs located at the bottom and those at the villus apex in term of function: cryptal TCs would regulate the local cell proliferation; those along the villus axis would mediate cell differentiation.…”
Section: Telocytesmentioning
confidence: 99%
“…TCs are a heterogenous population [ 4 , 5 ] and express CD34 and PDGFRa, among other markers. Several roles have been hypothesized for TCs in tissue homeostasis, morphogenesis, regeneration and repair, including intercellular communication with the integration of tissue components by cell-to-cell-signalling or extracellular shedding vesicles and paracrine molecules [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], the control and organisation of the extracellular matrix [ 15 ], the creation of microenvironments within the tissues [ 17 , 18 , 19 ], structural support [ 17 , 20 , 21 , 22 , 23 , 24 , 25 ], endocytosis with the internalization of small particles [ 9 ], the control and regulation of other cell types [ 26 ], guidance to cell migration during development and the contribution of scaffolds [ 14 , 17 , 27 , 28 , 29 , 30 , 31 ], immunomodulation and immunosurveillance [ 27 ], the inhibition of apoptosis (inhibition of oxidative stress and prevention of cellular ageing) [ 26 , 32 ], neurotransmission (e.g., contribution of slow waves generated by interstitial cells of Cajal) [ 10 , 15 , 25 , 33 , 34 , 35 ] and the modulation of stem cells (control of their growth and differentiation) [ 21 , 27 , 36 , 37 ,…”
Section: General Characteristics Of Telocytes and Terminological Imentioning
confidence: 99%
“…Isolation and culture expansion of TCs are of great interest in the perspective of allowing future reliable morphofunctional in vitro investigations to gain fundamental insight into the functions of these peculiar type of interstitial cells. In fact, the majority of studies that have so far investigated TCs in physiologic and pathologic tissues are mainly descriptive and focused on the ultrastructural, morphologic, and immunophenotypic characterization of these cells within their resident tissues, leaving much of their proposed functions still a matter of debate [ 22 , 29 , 55 , 56 ]. In this regard, the ability of TCs to form complex interstitial networks and communicate with neighboring cells by establishing multiple intercellular contacts or releasing extracellular vesicles containing bioactive molecules, together with the evidence that such TC networks are severely impaired in a variety of pathologies, led to proposing that these cells may exert a wide spectrum of functions important for the maintenance of tissue homeostasis [ 2 , 4 , 5 , 10 , 28 , 29 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%